Nilai-Nilai Agama Islam dalam Budaya dan Adat Masyarakat Aceh - Cut Muthia (Jurnal Riset Komunikasi Penyiaran Islam, 2021)
Abstract. This study aims to find out how Islamic values ​​are in the social, cultural situation of the people of North Kluet District, South Aceh Regency, Aceh Province. In North Kluet itself there are three ethnicities, three languages, who know each other. Not only that, there are also religious rituals and cultural rituals that are claimed to uphold Islamic values. The type of research conducted using ethnographic methods, with a descriptive qualitative approach that is descriptive analysis. Data was collected using the methods of observation, interviews, documentation, and literature. Overall, the results of this study give rise to theories, namely the existence of cultural integration, multicultural communication contained in social situations, as well as Islamic religious values ​​in the North Kluet district community. The role of Islamic values ​​in fact has an effect on the social situation of the people of North Kluet District, which is also very influential in every culture of the North Kluet community. These three aspects (social, cultural and Islamic) in the North Kluet region can be said to be Local Wisdom. So that Islamic values ​​that exist in the community of North Kluet District, South Aceh Regency, are able to influence the culture and social of the local community, thus creating Islamic culture and customs. Abstrak. Penelitian ini bertujuan untuk mengetahui bagaimana nilai- nilai Islam dalam situasi sosial, kebudayaan masyarakat Kecamatan Kluet Utara Kabupaten Aceh Selatan Provinsi Aceh. Di Kluet Utara sendiri terdapat tiga etnis, tiga bahasa, yang saling berdampingan. Tidak hanya itu, terdapat juga ritual keagamaan serta ritual kebudayaan yang di klaim menjungjung tinggi nilai-nilai Islam. Adapun jenis penelitian yang dilakukan menggunakan metode etnografi , dengan pendekatan kualitatif deskriptif yang bersifat deskriptif analisis. Pengumpulan data dilakukan dengan menggunakan metode observasi, wawancara, dokumentasi, dan kepustakaan. Secara keseluruhan, hasil penelitian ini memunculkan implikasi teoritis, yaitu adanya keterpaduan budaya, komunikasi multikultural yang terdapat dalam situasi sosial, serta nilai-nilai agama Islam pada masyarakat kec.Kluet Utara. Peran nilai – nilai Islam nyatanya berpengaruh dalam situasi sosial masyarakat Kec.Kluet Utara juga sangat berpengaruh dalam setiap kebudayaan pada masyarakat Kluet Utara. Ketiga aspek (sosial,budaya dan Islam) di wilayah Kluet Utara ini dapat dikatakan sebagai Kearifan Lokal. Sehingga nilai – nilai Islam yang berada di masyarakat Kec.Kluet Utara Kab.Aceh Selatan, mampu mempengaruhi budaya serta sosial masyarakat setempat, sehingga menciptakan budaya dan adat Islami.